IMPLEMENTASI BLENDED LEARNING PADA MASA PANDEMI COVID-19 DI SMAN 4 PANDEGLANG - Prihatini, Eneng Nurul; Kuntari, Septi (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
The Covid-19 phenomenon encourages learning activities to be held boldly to reduce community mobility as one way to reduce the potential for the spread of Covid-19. With the emergence of a new habitus in the world of education, there are new models of learning in the pursuit of learning effectiveness. one of them is the application of the Blended Learning model, which is a combination of two learning models, namely online (in a network) and face-to-face meetings (face to face). This study aimed to determine how the implementation of the Blended Learning model at SMAN 4 Pandeglang. This research uses a descriptive qualitative research method, and observation, interviews, and documentation do the data collection. The results show that the process of implementing blended learning at SMAN 4 Pandeglang starts from planning by planning a schedule, developing strategies and teaching materials, and compiling an evaluation model; the implementation process has two forms, namely 30% Blended Learning by presenting students who have inaccessible access and courageous learning facilities. The second is 50% Blended Learning with 50% bold learning and 50% face-to-face; Blended Learning is also applied in sociology learning. The benefits of implementing blended learning are (1) reducing problems in bold learning, (2) making it easier for teachers to provide direct assessments, (3) motivating students (4) improving student learning outcomes. The evaluation model of blended learning is divided into two, face-to-face evaluation and evaluation through a bold platform.